Mobile multimedia communications concepts, applications, and challenges - Karmakar 1970-; Dooley 1959- (Premier reference source, 2008)
"This book captures defining research on all aspects and implications of the accelerated progress of mobile multimedia technologies. Topics include fundamental network infrastructures, modern communication features such as wireless and mobile multimedia protocols, personal communication systems, mobility and resource management, and security and privacy issues. This book will meet the needs of researchers in a variety of fields"--Provided by publisher.